An Action Research on the Effectiveness of We-CARE Project (Comprehensive Activities for Remedial Enhancement): A Review Study - Alpapara, Loren S. (ASEAN Journal of Educational Research and Technology, 2023)
Remedial programs address learning gaps by reteaching basic skills. They focus on core areas, like English, Mathematics, and Science. Remedial programs are open to all students, including those with disabilities.  It has been noticed that in every quarterly examination the prevalent concerns among the subject teachers are the least mastered skills in every subject area. Every school had conducted a series of innovations to ascertain all the possible ways to reinforce students’ failure to meet the required performance level in all the subject areas. Since this concern is one of the most eyed by the Department of Education, Teachers should conduct remediation as mandated by DO 8, s. 2015, known as  Policy Guidelines on Classroom Assessment for the K to 12 Basic Education Curriculum when a learner receives a grade lower than 75 in any subject and had no performance task/s in 1st, 2nd, 3rd, or 4th quarters must be given intervention through remediation and must pass to be promoted to the next grade level. Also, with the implementation of the K to 12 Basic Education Curriculum, RA10533 to produce globally competitive graduates, ensuring all the skills and knowledge to pass is a must. So, this action research was conducted.